Enhance antibacterial effects of combination sodium diacetate and surfactant agent on Staphylococcus aureus and Escherichia coli and quality of fresh chilled ground pork - Akapakul, N. (2020)
Staphylococcus aureus and Escherichia coli are important foodborne pathogenic bacteria and serious intimidations to human health worldwide. This study was to reduce and control growth of S. aureus and E. coli and the spoilage bacteria in fresh ground pork stored at 5 and 15°C using sodium diacetate (SD) alone and in combination with polyethylene glycol (PEG). Microbial and physical qualities of ground pork (inoculated with S. aureus and E. coli 4log cfu/g) added 0.25%SD, 1.25%SD and 0.16%SD in combination with 0.16%PEG were investigated. The results showed that the adding 1.25%SD and 0.16%SD in combination with 0.16%PEG could significantly (p < 0.05) reduce S. aureus, E. coli, aerobic plate count (APC) and psychrotrophic bacteria population in ground pork. The both treatments could control growth of both pathogenic bacteria in ground pork stored at 5° C for 14 days. In addition, these treatments could control growth of S. aureus and E. coli stored at 15°C for 4 and 6 days, respectively. The adding both treatments could control growth of APC and extend shelf life of ground pork stored at 5 and 15°C for 12 and 8 days, respectively. However, the low pH of high concentration SD alone caused the highest weight loss and discoloration. No adverse effect of low concentration SD in combination with PEG in ground pork was observed. Its weight loss and color was not significantly different from those of non-treated at both storage temperatures (p > 0.05). Hence, this study suggests that 0.16%SD in combination with 0.16%PEG has great potential to be used as a good preservative for fresh chilled ground pork.